In pursuit of carbon neutrality : energy law and regulation in China / Hao Zhang, The Chinese University of Hong Kong. - Zhang, Hao (Law teacher) (Cambridge studies on environment, energy and natural resource governance., 2024)
China's goal of carbon neutrality by 2060 requires a significant transformation of energy systems and the economy, raising critical questions about the domestic energy legal and regulatory systems. This book critically analyses the development and implementation of energy laws and regulations related to crucial strategies and pathways towards carbon neutrality, namely decarbonising power supply, enabling fuel switching, electrifying end-use in transport and industry, and adopting carbon removal mechanisms. It offers rich legal details and insights into regulatory processes and arrangements that underpin energy market reform and liberalisation, while also examining the role of law and regulatory measures in promoting technological advancements and supply chains for decarbonisation, with a focus on renewable energy, energy efficiency and storage, electric vehicles, critical transition minerals and carbon removal mechanisms.